ANALISIS KEBUTUHAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROJECT BASED LEARNING BERNUASA KRISTIANI PADA MATERI KEANEKARAGAMAN HAYATI UNTUK SMA - Yosephine Manalu; Ardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop Christian-themed Project based learning (PjBL) Student Worksheets (LKPD) on Biodiversity for high school students. LKPD is designed to support the development of students' character and competencies in accordance with the Pancasila Student Profile, by integrating cognitive, spiritual, and Christian values. Biodiversity material was chosen because of its relevance to global issues of environmental conservation and sustainability. This study used a qualitative and quantitative descriptive approach conducted at Xaverius Catholic High School, Padang. The research subjects consisted of a Biology teacher and 80 students of grade X Phase E. The results of the needs analysis showed that 86.67% of students still had a basic understanding of the concept of biodiversity, and the rest admitted to having difficulties memorizing scientific names, distinguishing species, and grouping living things. A total of 93.33% of students stated that they were more motivated to learn through relevant real projects, and 100% of students saw a connection between biodiversity conservation and Christian teachings. Interviews with biology teachers also confirmed that the dominant teaching methods are lectures, discussions, and cooperative learning, while the PjBL model is rarely implemented, and there has been no development of Christian-themed student worksheets (LKPD) at this school. Therefore, the development of Christian-themed PjBL-based LKPDs is urgently needed to aid understanding of the material, foster gratitude, strengthen faith, and foster students' responsibility for the preservation of God's creation.